The effect of endurance exercise and rosehip extract supplementation on the expression of P53 and cytochrome C genes in male rat heart - Mitra Abdollahi-Diba; Jabar Bashiri; Hadi Pourmanaf; Vahid Fekri-Kourabbaslou (Journal of Cardiovascular and Thoracic Research, 2022)
Introduction: Considering the effect of Apoptosis on cardiovascular disease, this study aimed to determine the combined effect of endurance exercise and rosehip extract supplementation on the expression of P53 and cytochrome C genes in the myocardium of male rats. Methods: A total of 35 male rats were randomly divided into five groups (n=7) as follows: endurance exercise+rosehip extract supplementation (Ex+Supp), endurance exercise (Ex), rosehip extract supplementation (Supp), six-month control (Con2), and three-month control (Con). The subjects in Ex+Supp and Ex groups performed endurance exercise (running on a treadmill at 24-33 m/min for 10-60 min) for 12 weeks, five times a week. Subjects in Ex+Supp and Supp groups consumed 1000 milligrams/ kilogram of rosehip extract for 12 weeks. Also, Con and Con2 groups did not receive any intervention. To RNA extraction and synthesis cDNA and evaluate the P53 and cytochrome C genes of the myocardium of rats, RT-PCR analysis was used. Results: Neither endurance exercise nor rosehip alone nor together significantly affected the expression of cytochrome C and P53 genes in the heart muscle of male rats (P˃ 0.05). Also, endurance exercise (P=0.001) and rosehip supplementation (P=0.002) alone and in interaction (P<0.01) had a significant effect on body weight, myocardium weight, and the ratio of myocardium weight to body weight in male rats. Conclusion: Twelve weeks of endurance exercise accompanied with rosehip extract did not significantly affect the expression of P53 and cytochrome C genes. Further studies are suggested to confirm these results.